Selection of habitat by a marine amphipod. (10th May 2013) - Gestoso, Ignacio; Olabarria, Celia; Troncoso, Jesús S.
Abstract: Marine algae are known to provide habitats for a wide range of marine organisms. Populations of marine epiphytal invertebrates are generalists and are less adapted to live in only one macroalga species. However, there are some examples of local adaptation and, in particular, amphipods have shown strong host specificity. Amphitholina cuniculus, an amphipod with an alga‐burrowing habit, has been mainly observed in Bifurcaria bifurcata mats on the intertidal rocky shores of the southern region of the Galician coast (NW Spain; 42º11.27′ N, 8º48.25′ W). We designed a laboratory experiment conducted in June 2009 to analyse the association between the amphipod and the macroalga. In particular, we hypothesised that (i) this species would exhibit different behaviour during the day and at night, and (ii) adults of A. cuniculus would prefer B. bifurcata as habitat rather than Fucus vesiculosus or Sargassum muticum . Results supported the hypothesis that adults of A. cuniculus preferred B. bifurcata, although such preferences did not show the day/night variability predicted. This amphipod might be considered a specialist species, at least on rocky intertidal shores along the Galician coast.